Bioaccumulation of trace metals in banded Persian bamboo shark (Chiloscyllium arabicum) from the Persian Gulf: A food safety issue. (March 2018) - Adel, Milad; Copat, Chiara; Saeidi Asl, Mohammad Reza; Conti, Gea Oliveri; Babazadeh, Mehdi; Ferrante, Margherita
Abstract: Persian bamboo shark ( Chiloscyllium arabicum ) was collected from two sites of the Khozestan province, northern basin of Persian Gulf, with the aim to identify differences in metal concentrations between fishing areas as well as the risk for human health due to consumption of the selected species. We analyzed Zn, Cu, Pb, Hg, Cd and Ni in muscle and liver tissues of specimens from both areas of study using atomic adsorption spectrometry. Statistical elaborations revealed higher bioaccumulation of metals in livers than muscle as well as in the site of worthy of Musa as regards Zn, Pb and Ni than the site of worthy of Darvis, due to the more intensive anthropogenic input. The risk for consumers is low for the most of metals, with the exception of the THQ for Hg, which resulted next to the level of risk with high frequencies of consumption.